Multi-Domain Concept of Using A2/AD Capabilities in the Military Strategy of the Russian Federation - Mirosław Banasik (Polish Political Science Yearbook, 2023)
This article presents the results of research, which set out to clarify the importance and role played by the concept of using A2/AD capabilities in the military strategy of the Russian Federation. Analysis and criticism of the literature were used to solve the research problems. In order to guide the research process, a hypothesis was formulated, assuming that the Russian concept of using A2/AD capabilities is an operationalisation of a broader military strategy for defeating the adversary, as well as an effective deterrence mechanism. The research process established that the Russian concept of using A2/AD capabilities is a theory and operational practice, a broader military strategy of achieving multi-domain superiority over the adversary by conducting strategic offensive operations. Integrating offensive and defensive operational capabilities plays a key role in this concept, which guarantees possession of the strategic initiative and maintenance of dominance in the international security environment and supports the idea of creating Russian spheres of influence. It also prompts NATO states to counter the supremacy of the Russian Federation.